SIFAT PAPAN SEMEN SABUT KELAPA - Rozak Memed; Paribotro Sutigno; I M Sulastiningsih (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
The report deals with laboratory tests on the properties of cement board made from coconut husk bonded with Portland cement. The test includes board density, moisture content. thickness reduction due to and bending strength.The result reveals that the physical and mechanical properties of cement board made with Ca(OH)2 and K2SO4) Al2 (S04)3 mineralizing fluid produces better quality board compared with that using CaCl2. The physical and mechanical properties of cement boards with Ca(OH)2 and (K2SO4) Al2 (S04)3 conform to the DIN 1101 standard. The bending strength of cement board made with CaCl2 does not conform to the DIN 1101 standard.